Predicting the Risk of Mortality for Patients Diabetic with Coronavirus Disease (COVID-19): A Retrospective study - Dharma Lindarto; Ginting, Fransiscus (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background. One of the biggest causes of mortality of patients diabetic with COVID-19 in the globe is diabetes mellitus. The study's goal was to examine the predicting the risk of mortality for patients diabetic with coronavirus disease (COVID-19). Methods. This is a retrospective study of patients diabetic with COVID-19 on 22 June 2020 to 21 July 2021 in H. Adam Malik Hospital Medan from 22 June 2020 to 21 July 2021. We collected all the data from electronic medical records on diabetics with SARS-CoV-2 infection, including demographic, clinical, laboratory, and radiological characteristics, treatments, complications, and clinical outcomes. All patients had throat swabs taken from their upper respiratory tracts to determine whether they had SARS-CoV-2 infection. Diagnosis of diabetes mellitus used ADA criteria. Results: There were 163 diabetic patients with COVID-19, consisting of mild (0%), moderate (39.8%), severe (44.2%), and critical (16.5%), and the most comorbid disease is hypertension. There was a significant age difference, length of stay, blood routine, and certain inflammatory markers between patients Diabetic with COVID-19 discharged from the hospital and died (all, p<0.05). The predicted death of patients diabetic with COVID-19 was D-dimer (OR: 4.069; p=0.008*;95% C.I: 1.43-11.55) and dexamethasone use (OR:4.769; p=0.007*; C.I: 1.54-14.71). Conclusion. The use of dexamethasone and the increase of D-dimer values increase mortality predictions in treating diabetic patients with COVID-19 in hospitals. To prevent these harms, the management of inpatients diabetic with COVID-19 must be with good glucose consideration and monitoring.